Development of a protocol for the regeneration of protoplasts from cassava (Manihot esculenta) isolated from friable embryogenic callus. - Bueno, Angie M; Sanchez, Francisco J; Buritica, Magdalena; Chavarriaga, Paul (2024)
Development of a protocol for the regeneration of protoplasts of cassava (Manihot esculenta) isolated from friable embryogenic callus.